The impact of a moderate exercise programme on serum interleukin-2 and interleukin-4 levels among secondary school children - Ludin, Arimi Fitri Mat (2001)
Cytokines are soluble glycoproteins that mediate cotntnunication between and within imn1une and non-imtnune cells. An alteration of cytokine production will impair the i1nrnune response and function. Previous studies on the itnpact of exercise on cytokines have not been conclusive. Most studies were centered on adults and there is a lack of data about the correlation between exercise and cytokines on adolescents. The purpose of this investigation therefore, was to detennine the effect of tnoderate exercise on some cytokine levels in adolescence.